PENERAPAN ALAT MUSIK MELODI PIANIKA DALAM MENINGKATKAN KECERDASAN MUSIKAL ANAK USIA 5-6 TAHUN - Putri Clawson; Diana Marita (P3M STKIP 'Aisyiyah Riau, 2017)
This research is motivated by the low level of children's musical intelligence at Kindergarten Aisyiyah Bustanul Athfal V Pekanbaru, and the learning that teachers use to improve musical intelligence is not yet interesting. The method used in this research is Classroom Action Research with a total of 25 research subjects consisting of 10 boys and 15 girls. Data collection techniques data collection in this study is observation and documentation. The data analysis technique used in this study is the percentage technique. The results of the study conducted, showed that the activity of teachers in the first cycle obtained a percentage score of 48.2%. The observation of teacher activities in the second cycle showed an increase with a percentage score of 85.7% with good criteria. Increased teacher activity can increase children's activity, in cycle I obtained a score of 56.5 (56.5%) with poor criteria. In cycle II with a score of 82.9 (82.9%) with good criteria. Increased activity of students is followed by an increase in musical intelligence in children, from cycle I to cycle II. in cycle I obtained an average score of 37.8 (47%) with kiteria starting to develop. An increase in musical intelligence increased in children in Kindergarten Aisyiyah Bustanul Athfal V Pekanbaru in the second cycle with an average score of 47.8 (78.5%) with very well developed criteria (BSB).